Biochar-assisted rapid formation of core–biofilm anammox granules via interfacial trapping of extracellular polymeric substances - Jingwei Fu; Yue Li; Yaqian Liu; Can Xiong; Pei Li; Xuanqi Long; Qian Li; Rong Chen (Bioresource Technology, 2026)

Impacts of high-altitude aerosol hygroscopicity on cloud microphysics in the North China Plain: A WRF fast-SBM modeling study - Qian Gao; Hui He; Xiang'e Liu; Yan Yang; Rong Yuan; Ping Tian; Kai Bi; Fei Wang; Jiujiang Sheng; Yongqing Wang (Atmospheric Research, 2026)

Biochar promotes methane production from anaerobic digestion: Pore structure regulation and quantitative correlation assessment - Ze-Mu Li; Ai-Hua Li; Cong-Cong Tang; Qian Li; Ai-Juan Zhou; Wenzong Liu; Zhi-Ling Li; Zhang-Wei He; Rong Chen (Bioresource Technology, 2026)

Differential stability and adaptive recovery of two-stage partial nitritation–anammox system treating pilot-scale food waste-derived anaerobic membrane bioreactor permeate - Xifang Tang; Shuangquan Zhao; Yihang Li; Yaqian Liu; Hongzhi Chen; Qian Li; Rong Chen (Bioresource Technology, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Reaction-generated secondary phase advances electronic-phonon decoupling and boosted mechanical performance in Bi0.42Sb1.58Te3 alloys - Yi-lin Liu; Hao Liang; Chong-Yu Wang; Jiang-Hu Yu; Kang Yue; Qian Deng; Ju Rong; Jing Feng; Zhen-Hua Ge (Chemical Engineering Journal, 2026)

Optimizing lipid retention for anaerobic membrane bioreactors treating food waste: Balancing methane enhancement and membrane fouling control - Luwei Yan; Shuangquan Zhao; Yu Xi; Yaqian Liu; Yuxin Xiao; Zhen Lei; Qian Li; Rong Chen (Bioresource Technology, 2026)

Taxonomy of Neostagonosporella on Chimonobambusa with descriptions of two new taxa - Xiu-Lan Xu; Yu Deng; Li-Ping Gao; Qian-Ying Huang; Wei Liu; Li Zhuang; Fei Chen; Qian-Gang Xiao; Zhen Zeng; Feng Liu; Qi-Rong Sun; Ying-Gao Liu; et al. (Mycological Progress, 2026)

Unraveling antibiotic fate in a highly urbanized estuary: Spatiotemporal patterns, multi-media partitioning, and contaminant prioritization - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Xiao-Ping Huang (Marine Pollution Bulletin, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Antidiabetic effects of Achyranthes bidentata polysaccharides: association with of gut microbiota and intestinal barrier function - Yaju Di; Yanan Liu; Yiwei Yang; Yuan Qian; Xiaohu Luo; Rong Ge; Lingling Jia (Food Bioscience, 2026)

Enzymatically synthesized native-like guaiacyl dehydrogenation polymer as a formaldehyde-free adhesive for high-strength, water-resistant plywood - Rui Luo; Wenhao Liu; Qian Tu; Yuanpu Wang; Junjun Chen; Junxian Xie; Rong Zhang; Nianjie Feng; Peng Wang (Chemical Engineering Journal, 2026)

HDAC inhibition reprograms stem cell fate to suppress infantile hemangioma vasculogenesis - Qiming Chen; Hao Rong; Chao Liu; Jiang Li; Jiawei Zheng; Qian Bian (Angiogenesis, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

A multicomponent Fc-fused subunit vaccine induces cross-protective immunity against porcine reproductive and respiratory syndrome virus QYYZ-like and NADC30-like strains - Linxing Tian; Zhengdan Lin; Mengxi Pan; Yanwen Wen; Mingxing Lu; Shudan Liu; Chao Zhang; Zhenxiang Rong; Jiahui Ma; Ruiqu Zhou; Nan Cao; Xinghua Chen; et al. (Veterinary Microbiology, 2026)

Insights to how tubular pore biochar affects anaerobic digestion of waste activated sludge: Performances and mechanisms - Ze-Mu Li; Ai-Hua Li; Qing-Bin Meng; Cong-Cong Tang; Qian Li; Ai-Juan Zhou; Wenzong Liu; Zhi-Ling Li; Zhang-Wei He; Rong Chen (Bioresource Technology, 2026)

Mechanism of the quasi-biweekly precipitation variability over the Mongolian Plateau and its simulations in CMIP6 models - Yepeng Xiao; Yingxia Gao; Rong Li; Yitian Qian; Xiaodong Liu (Atmospheric Research, 2026)

SVA virus-like vesicle vaccine based on VEEV-VSVG vector elicits efficient immune responses and protection in swine - Zhenxiang Rong; Mingjin Jiao; Nan Cao; Mingxing Lu; Shudan Liu; Chao Zhang; Liuqing Wei; Yamei Li; Huanchun Chen; Xiangmin Li; Ping Qian (Veterinary Microbiology, 2026)

Lengthening vegetation carbon turnover time across China’s forests - Rong Ge; Xiaoli Ren; Honglin He; Guirui Yu; Li Zhang; Qian Xu; Mengyu Zhang; Shilong Piao; Kailiang Yu; Mathew Williams; Xiaobo Zhu; Shiyong Yu; et al. (Science Bulletin, 2026)

Multi-omics reveals that Sophora alopecuroides lysine decarboxylase (SaLDC)-mediated polyamine metabolism enhances salt tolerance and early flowering in Arabidopsis - Yongli Tian; Rui Wang; Jing Su; Wenjuan Li; Ping Liu; Chengke Luo; Jiaojiao Qian; Danting Zhang; Peifu Li; Bin Wang; Rong Yang; Tianli Ma; et al. (Plant Science, 2026)

New mechanistic insights into the antiviral candidate CA-P: Activation of plant redox-mediated defense and suppression of virus biosynthesis - Rong-Shuang Luo; Yan-Wei Huang; Yu-Cheng Gu; Long Cheng; Wu-Bin Shao; Yan-Mei Liao; Qian Guo; Dan Zeng; Hong-Mei Xiang; Xiang Zhou; Li-Wei Liu; Zhi-Bing Wu; et al. (Pesticide Biochemistry and Physiology, 2026)

Mechanism of macrophage mitochondrial transfer in CBNPs induced EndMT of pulmonary microvascular endothelial cells - Mengruo Wang; Qian Wang; Qingping Liu; Shanshan Zhang; Yujia Xie; Tao Zhang; Ze Yang; Lei Bao; Yaxian Pang; Dongxing Shi; Jiaji Cheng; Yujie Niu; et al. (Journal of Hazardous Materials, 2026)

Mechanisms of failure and permeability evolution in gas-bearing strata under tunnel-induced stress paths - Jiafeng Tan; Deyi Jiang; Rong Liu; Yi He; Jinyang Fan; Jianyu Liang; Cheng Qian; Hanlin He; Hong Zheng (Transportation Geotechnics, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Bionic cellulose fiber-based columnar solar evaporator with interfacial regulation for superfast water purification - Ying Qian; Zhexuan Lan; Shunfang Wen; Rong Liu; Haifeng Zhang; Ruiqing Li; Du Nie; Seeram Ramakrishna; Wei Zhang; Jiamu Dai (Desalination, 2026)

Constructed wetland substrate–mediated stereoselective transformation of metolachlor: Influence of redox conditions and microbial community dynamics - Liangjin Chen; Yucong Zheng; Mawuli Dzakpasu; Qian Yang; Guochen Liu; Liping Zhao; Tianfu Wu; Dongfu Zhang; Xiaochang Wang; Rong Chen (Environmental Research, 2026)

Screening of Fecal Bacteroides Strains and Discovery of Bacteroides eggerthii S13-F8 with Protective Effects Against Chemotherapy-Induced Diarrhea - Yi Zhao; Zhengqun Dai; Yanmei Lang; Rui Li; Hongyu Zheng; Jiajia Mi; Xiu He; Jin Liu; Rong Xiang; Xueran Mei; Yang Liu; Yantang Wang; et al. (Probiotics and Antimicrobial Proteins, 2026)

Astrocyte-Derived CXCL10 Induces Neuronal Tau Hyperphosphorylation and Cognitive Impairments in Sepsis - Cuiping Guo; Hang Ruan; Wensheng Li; Yi Liu; Abdoul Razak Yacoubou Mahaman; Qian Guo; You Zhou; Rong Liu; Jianzhi Wang; Chenliang Zhou; Xiaochuan Wang; Shusheng Li (Neuroscience Bulletin, 2026)

Effects and mechanisms of Klebsiella aerogenes HC10 on antimony accumulation in Brassica napus - Qian Zhang; Kai Zhong; Caiyuan Ling; Congyao Shi; Junyu Xiang; Zhongning Liu; Qun Rong; Chaolan Zhang (Applied Soil Ecology, 2026)

Unlocking synergy in thermophilic co-digestion of rice straw and food waste: boosting biogas production through accelerated kinetics and substrate biodegradability - Yaqian Liu; Ryoya Watanabe; Qian Li; Yutong Luo; Naohito Tsuzuki; Yu Qin; Rong Chen; Yu-You Li (Journal of Environmental Management, 2025)

Advances in acetylcholinesterase-based biosensing technologies for organophosphorus pesticide detection: A comprehensive review (2020–2024) - Qian Zhang; Jing Yu; Yanping Wei; Rong Yang; Jin Liu; Yangyang Su; Die Gao; Jing Zeng (Food Chemistry, 2025)

Integrated Geology-Geophysics Exploration of Rare Metal Deposits in the Yidun Island Arc Collisional Orogen - Rong Yang; Yu Peng; Li Qing; Qian-kun Liu; Xue-feng Hao; Han Wu; Jun-bo Fan; Hong-juan Chen; Tao Yang (Applied Geophysics, 2025)

Four new phenolic constituents from root barks of Paeonia ostii - Qian-Qian Meng; Yi Su; Shun-Yao Tong; Xing-Rong Peng; Jun-Chen Zhu; Ji-Kai Liu (Natural Product Research, 2025)

Orbital-engineering-enabled electrified ferrocene–FeOOH membrane for effective flow-through organoarsenic mineralization and arsenic sequestration - Xin Gao; Qian Li; Rong Chen; Xuefeng Liu; Lin Yang; Yongshen Hou; Hao Sun; Yanbiao Liu; Haitao Wang; Yi Wang (Chemical Engineering Journal, 2025)

Navigating the lunar frontier: one hundred landing sites at the south pole for future mission challenges - Yongjiu Feng; Pengshuo Li; Haoteng Li; Yan Liu; Mengrong Xi; Rong Wang; Shurui Chen; Panli Tang; Yuze Cao; Qian Huang; Qionghua You; Shijie Liu; et al. (Science Bulletin, 2025)

CTAB-Assisted, controlled preparation of a CeZrOx/CuSAPO-34 catalyst and its performance for the synergistic removal of NOx and toluene from flue gas - Qian Zhou; Xuehui Jia; Rong Liu; Fangfei Liu; Han Zhang; Dan Hou; Lu Wang; Yunkuo Luo; Bichun Huang; Hong Huang; Xia Gong; Chenglong Yu (Journal of Environmental Chemical Engineering, 2025)

Iron sulfide mineral/polylactic acid mixotrophic biofilter for simultaneous nitrate and phosphate removal - Yuwei Zhang; Xueyu Liu; Shiyang Wang; Rong A; Shujie Qian; Yaquan Liang; Yonglan Tian; Dongyang Wei; Huayong Zhang (Journal of Environmental Sciences, 2025)

Elucidation of the anti-fibrotic diseases mechanism of chelerythrine by integrative approach of network pharmacology and experimental verification - Wei Han; Gui-yun Qian; Qin-rong Wang; Jie Liu; Yong-ping Zhang; Jian Xu; Tingting Li; Zhe Li (Natural Product Research, 2025)

Extending the Mutational Spectrum of SYNE1 Ataxia in Chinese Patients - Xin Huang; Zhao Chen; Qian Jiang; Panyan Liu; Yiqing Gong; Lijing Lei; Jia Chen; Chunrong Wang; Linlin Wan; Lang He; Linliu Peng; Rong Qiu; et al. (The Cerebellum, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Electroacupuncture may alleviate diabetic neuropathic pain by inhibiting the microglia P2X4R and neuroinflammation - Si-ying Qu; Han-zhi Wang; Qun-qi Hu; Yi-qi Ma; Yu-rong Kang; Li-qian Ma; Xiang Li; Lu-hang Chen; Bo-yu Liu; Xiao-mei Shao; Bo-yi Liu; Jun-ying Du; et al. (Purinergic Signalling, 2025)

Exploring morphological heterogeneity of circulating tumor cells: machine learning-based approach for cell identification and prognostic implications - Peng-Xiang Wang; Yu-Chen Zhong; Bin Duan; Jian-Wen Cheng; Yun-Fan Sun; Wen-Jing Zheng; Kai-Qian Zhou; Yang Xu; Hai-Xiang Peng; Wei-Xiang Jin; Hai-Min Li; Xiao-Juan Sun; et al. (Science Bulletin, 2025)

Neuroprotective lindenane sesquiterpenoids from the roots of Lindera aggregata (Sims) Kosterm - Lie-Feng Ma; Shan-Rong Luo; Qian-Qing Liu; Rui-Si Tang; Ning-Yu Chen; Di Luo; Lu Guo; Jia Li; Rui Wu; Zha-Jun Zhan (Phytochemistry, 2025)

Plant and microbial β diversities are better predictors of ecosystem functioning than their α diversities, but aridity weakens these associations - Lu Zhang; Shilong Lei; Rong Qian; Raúl Ochoa-Hueso; Xiangtao Wang; Jie Wang; Lirong Liao; Guobin Liu; Qiang Li; Chao Zhang (Plant and Soil, 2025)

Corrigendum to “Stable isotope tracing reveals glucose metabolism characteristics of drug-resistant B-cell acute lymphoblastic leukemia” [Analytica Chimica Acta 1352 (2025) 343884] - Rong Hu; Zhengwei Duan; Mengyao Wang; Mengting Liu; Yaoxin Zhang; Yanxi Lu; Yuhan Qian; Enjie Wei; Jianghua Feng; Pengfei Guo; Yang Chen (Analytica Chimica Acta, 2025)

High-efficiency immobilization of soil available cadmium by chicken manure and its derivatives: Roles of chemical and microbial property - Zhi-Wen Hu; Feng Jiang; Fei Huang; Heng Wang; Qian-Jun Liu; Xiao Zhou; Ming-Zhi Huang; Peng Wang; Rong-Bo Xiao (Journal of Environmental Chemical Engineering, 2025)

A high-performance flexible force sensitive conductive composite with programmed digital crack by femtosecond laser etching - Rong Zhang; Xuejiao Shen; Deyuan Lou; Chaoshuai Dong; Qingyan Liu; Qian Liu; Qingting Liu; Xudong Fu; Shengfei Hu (Chemical Engineering Journal, 2025)

Glymphatic Impairment Associated with Neurocognitive Dysfunction in Moyamoya Disease - Chaofan Zeng; Yuanren Zhai; Peicong Ge; Chenglong Liu; Xiaofan Yu; Wei Liu; Junsheng Li; Qiheng He; Xingju Liu; Xun Ye; Qian Zhang; Rong Wang; et al. (Translational Stroke Research, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Stable isotope tracing reveals glucose metabolism characteristics of drug-resistant B-cell acute lymphoblastic leukemia - Rong Hu; Zhengwei Duan; Mengyao Wang; Mengting Liu; Yaoxin Zhang; Yanxi Lu; Yuhan Qian; Enjie Wei; Jianghua Feng; Pengfei Guo; Yang Chen (Analytica Chimica Acta, 2025)

Vertical distributions of dimethyl sulfide and dimethylsulfoniopropionate and impacts of DMSP lyase and bacteria in the Yellow Sea and East China Sea - Xin-Ran Song; Qian-Yao Ma; Juan Yu; Gui-Peng Yang; Rong Chen; Zheng-Yu Zhang; Yu Jiang; Long-Fei Liu (Marine Environmental Research, 2025)

Hidden threat in turbid waters: Quantifying and modeling the bioaccumulation and risks of particulate metals to clams - Jing Qian; Xue Cao; Haiyan Xiong; Fengjie Liu; Minwei Xie; Rong Chen; Qiao-Guo Tan (Environmental Pollution, 2025)

Climate change enhances greening while human activities accelerate degradation in northern China's grasslands - Feifei Cao; Leizhen Liu; Yuping Rong; Nan Jiang; Lin Zhao; Qian Zhang; Zhitao Wu; Wenhui Zhao; Sheng Li (Science of The Total Environment, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

LINC01224 promotes the Warburg effect in gastric cancer by activating the miR-486-5p/PI3K axis - Yuling Bin; Minji Liu; Rong He; Pingfei Tang; Weiming Qu; Dajun Wu; Lin Tan; Qian Wang; Peng Jiang; Hongsai Hu (In Vitro Cellular & Developmental Biology - Animal, 2025)

Turning coal hydrogenation liquefaction residue into high conductivity carbon black with magnesium citrate-assisted steam activation followed by high temperature treatment - Qian Meng; Huiping Sun; Yiyang Rong; Mengxue Tang; Yan Tan; Ting Liu; Zizhen Ma; Huawei Zhang (Fuel, 2025)

Ternary Ni:Fe- activated inert Cu-based electrocatalyst as efficient bifunctional electrocatalysts for water splitting - Shi-Yu Lu; Chunjie Wu; Tingting Hu; Ling Wang; Wenzhao Dou; Jun Zhang; Rong Wang; Yin Liu; Qian Yang; Zhigang Zou; Meng Jin (Chemical Engineering Journal, 2025)

Transcription factor CcbHLH66 regulates mandarin fruit coloration via modulating the expression of chlorophyll degradation related genes CcRCCR and CcNYC - Huali Wang; Qian Liu; Shufang Deng; Jialin Chen; Jin Han; Rong Zhu; Kaifang Zeng; Lili Deng (Postharvest Biology and Technology, 2024)

Quantitative mechanisms for the Cd2+ adsorption increased by sewage-sludge biochar but decreased by rice-straw biochar after melamine modification - Zi-Xuan Yin; Yun-Yi Zhang; Jia-Xin Liu; Fei Huang; Qian-Jun Liu; Ming-Zhi Huang; Rong-Bo Xiao; Guo-Yi Gao; Tian-Zhen Lan; Xiao Zhou (Journal of Environmental Chemical Engineering, 2024)

Strong electronic interaction in chromium-molybdenum dual incorporated few-layer cobalt sulfide nanosheets with lattice distortion for efficient bifunctional water splitting - Shi-Yu Lu; Wenzhao Dou; Chunjie Wu; Jun Zhang; Ling Wang; Tingting Hu; Rong Wang; Yin Liu; Qian Yang; Meng Jin (Fuel, 2024)

Effects of different fermentation modes on tea leaves: Revealing the metabolites modification by quasi-targeted metabolomics - Xin Fang; Rong Xue; Jingyi Xiao; Qian Pu; Yufei Wang; Yuan Yuan; Bin Liu; Mengyuan Sui; Guangxian Jiang; Rida Niaz; Yongping Sun; Ziming Yu; et al. (Food Bioscience, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

Synergic treatment of domestic wastewater and food waste in an anaerobic membrane bioreactor demo plant: Process performance, energy consumption, and greenhouse gas emissions - Zhen Lei; Jiale Zheng; Jiale Liu; Qian Li; Jingjing Xue; Yuan Yang; Zhe Kong; Yu-You Li; Rong Chen (Water Research, 2024)

Dynamic changes in the aroma profiles and volatiles of Enshi Yulu tea throughout its industrial processing - Guangxian Jiang; Rong Xue; Jun Xiang; Yufei Wang; Bin Liu; Yuan Yuan; Qian Pu; Xin Fang; Xingming Hu; Xiaoying Liu; Youyi Huang (Food Chemistry, 2024)

Size-dependent influences of nano- and micro-plastics exposure on feeding, antioxidant systems, and organic sulfur compounds in ciliate Uronema marinum - Long-Fei Liu; Juan Yu; Yu Jiang; Qian Liu; Yong Jiang; Rong Chen; Gui-Peng Yang; Xin-Ran Song (Environmental Pollution, 2024)

Precipitation contributes to alleviating pollution of rubber-derived chemicals in receiving watersheds: Combining confluent stormwater runoff from different functional areas - Yue-Hong Liu; Yu-Xian Mei; Jing-Yi Wang; Shan-Shan Chen; Jia-Li Chen; Nan Li; Wang-Rong Liu; Jian-Liang Zhao; Qian-Qian Zhang; Guang-Guo Ying (Water Research, 2024)

Nomogram to Predict Good Neoangiogenesis After Indirect Revascularization Surgery in Patients with Moyamoya Disease: a Case–control Study - Kexin Yuan; Ke Wang; Haibin Zhang; Yunfan Zhou; Qiang Hao; Xun Ye; Xingju Liu; Qian Zhang; Yan Zhang; Rong Wang; Yuanli Zhao; Yahui Zhao (Translational Stroke Research, 2024)

The immunoadjuvant effects of interleukin-8 on Aeromonas veronii inactivated vaccine in largemouth bass (Micropterus salmoides) - Shun Yang; Qian-Rong Liang; Dao-Le Liu; Ze-Sheng Zhang; Yu-Hong Yang; Xiao-Fei Yao; Hui Fei (Aquaculture International, 2024)

Preliminary assessments of carbon release driven by Late Pleistocene Arctic ice sheets - Liming Ye; Xiaoguo Yu; Yeping Bian; Weijia Fan; Zhongqiang Ji; Sai Song; Ziyin Wu; Qian Ge; Dong Xu; Weiyan Zhang; Haiyan Jin; Xiaohu Li; et al. (Quaternary Science Reviews, 2024)

Biokinetic and microbial insights into regulatory mechanisms of long-chain fatty acid degradation during food waste-lipid co-digestion within anaerobic membrane bioreactor - Yaqian Liu; Yu Xi; Qian Li; Mawuli Dzakpasu; Rong Chen; Yu-You Li (Bioresource Technology, 2024)

TBC1D1 is an energy-responsive polarization regulator of macrophages via governing ROS production in obesity - Qi Wang; Ping Rong; Wen Zhang; Xinyu Yang; Liang Chen; Ye Cao; Minjun Liu; Weikuan Feng; Qian Ouyang; Qiaoli Chen; Hailong Li; Hui Liang; et al. (Science China Life Sciences, 2024)

Seasonal dynamics of the microbiota and nutritional composition in bee bread from Apis cerana and Apis mellifera colonies - Jia-Li Li; Wan-Li Li; Jun Zhang; Yan-tao Pang; Jian Xiong; Ping Wu; Bang-rong Wei; Xi-Jie Li; Qi Huang; Qi-He Tang; Chong-Hui Zhao; Qian Wang; et al. (Food Research International, 2024)

Mass cytometry revealed the circulating immune cell landscape across different Suzuki stages of Moyamoya disease - Chenglong Liu; Peicong Ge; Bojian Zhang; Liujia Chan; Yuheng Pang; Chuming Tao; Junsheng Li; Qiheng He; Wei Liu; Siqi Mou; Zhiyao Zheng; Zhikang Zhao; et al. (Immunologic Research, 2024)
Moyamoya disease (MMD) is a cerebrovascular disorder marked by progressive arterial narrowing, categorized into six stages known as Suzuki stages based on angiographic features. Growing evidence indicates a pivotal role of systemic immune and inflammatory responses in the initiation and advancement of MMD. This study employs high-dimensional mass cytometry to reveal the immunophenotypic characteristics of peripheral blood immune cells (PBMCs) at various Suzuki stages, offering insights into the progression of MMD. PBMC samples from eight patients with early-stage MMD (Suzuki stages II and III) and eight patients with later-stage MMD (Suzuki stages IV, V, and VI) were analyzed using high-dimensional mass cytometry to evaluate the frequency and phenotype of immune cell subtypes. We identified 15 cell clusters and found that the immunological features of early-stage MMD and later-stage MMD are composed of cluster variations. In this study, we confirmed that, compared to later-stage MMD, the early-stage MMD group exhibits an increase in non-classical monocytes. As the Suzuki stage level increases, the proportions of plasmacytoid DCs and monocyte-derived DCs decrease. Furthermore, T cells, monocytes, DCs, and PMN-MDSCs in the early-stage MMD group show activation of the canonical NF-κB signaling pathway. We summarized and compared the similarities and differences between early-stage MMD patients and later-stage MMD patients. There is a potential role of circulating immune dysfunction and inflammatory responses in the onset and development of MMD.

Fibroblast-localized lncRNA CFIRL promotes cardiac fibrosis and dysfunction in dilated cardiomyopathy - Shuai Yuan; Xudong Zhang; Jiabing Zhan; Rong Xie; Jiahui Fan; Beibei Dai; Yanru Zhao; Zhongwei Yin; Qian Liu; Dao Wen Wang; Huaping Li; Chen Chen (Science China Life Sciences, 2024)

Viperin inhibits interferon-γ production to promote Mycobacterium tuberculosis survival by disrupting TBK1-IKKε-IRF3-axis and JAK-STAT signaling - Yao Liang; Yun Liang; Qi Wang; Qianna Li; Yingqi Huang; Rong Li; Xiaoxin Pan; Linmiao Lie; Hui Xu; Zhenyu Han; Honglin Liu; Qian Wen; et al. (Inflammation Research, 2024)
Objectives and design As an interferon-inducible protein, Viperin has broad-spectrum antiviral effects and regulation of host immune responses. We aim to investigate how Viperin regulates interferon-γ (IFN-γ) production in macrophages to control Mycobacterium tuberculosis (Mtb) infection. Methods We use Viperin deficient bone-marrow-derived macrophage (BMDM) to investigate the effects and machines of Viperin on Mtb infection. Results Viperin inhibited IFN-γ production in macrophages and in the lung of mice to promote Mtb survival. Further insight into the mechanisms of Viperin-mediated regulation of IFN-γ production revealed the role of TANK-binding kinase 1 (TBK1), the TAK1-dependent inhibition of NF-kappa B kinase-epsilon (IKKε), and interferon regulatory factor 3 (IRF3). Inhibition of the TBK1-IKKε-IRF3 axis restored IFN-γ production reduced by Viperin knockout in BMDM and suppressed intracellular Mtb survival. Moreover, Viperin deficiency activated the Janus kinase (JAK)-signal transducer and activator of transcription (STAT) signaling pathway, which promoted IFN-γ production and inhibited Mtb infection in BMDM. Additionally, a combination of the anti-TB drug INH treatment in the absence of Viperin resulted in further IFN-γ production and anti-TB effect. Conclusions This study highlights the involvement of TBK1-IKKε-IRF3 axis and JAK-STAT signaling pathways in Viperin-suppressed IFN-γ production in Mtb infected macrophages, and identifies a novel mechanism of Viperin on negatively regulating host immune response to Mtb infection.

Synergistic effects of biochar addition and filtration mode optimization on mitigating membrane fouling in high-solid anaerobic membrane bioreactors - Chengfan Jiao; Hao Chen; Yaqian Liu; Hexiang Zhao; Qian Li; Gaojun Wang; Rong Chen; Yu-You Li (Science of The Total Environment, 2024)

Unravelling the safety improving and failure mechanisms of a 56.5 Ah high-energy–density Li-ion cell containing solid-state electrolyte - Wei Zhang; Xiaopeng Qi; Min Liu; Bingxue Liu; Yuansen Hu; Jing Ye; Rennian Wang; Bin Li; Changhong Wang; Qian Huang; Bing Yu; Rong Yang; et al. (Chemical Engineering Journal, 2024)

Biochar-mediated synergistic promotion of DIET and IHT: Kinetic and thermodynamic insights into propionate two-step syntrophic methanogenesis - Danyang Zhao; Peiyun Zhang; Yaqian Liu; Qian Li; Gaojun Wang; Rong Chen; Yu-You Li (Chemical Engineering Journal, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Seed germination and seedling growth response of Leymus chinensis to the allelopathic influence of grassland plants - Kaili Wang; Pengpeng Dou; Zhengzhou Miao; Jing Huang; Qian Gao; Lizhu Guo; Kesi Liu; Yuping Rong; Ding Huang; Kun Wang (Oecologia, 2024)

First insights into the bioaccumulation, biotransformation and trophic transfer of typical tetrabromobisphenol A (TBBPA) analogues along a simulated aquatic food chain - Chuan-Sheng Sun; Sheng-Wu Yuan; Rui Hou; Si-Qi Zhang; Qian-Yi Huang; Lang Lin; Heng-Xiang Li; Shan Liu; Yuan-Yue Cheng; Zhi-Hua Li; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

New insight into the bioaccumulation and trophic transfer of free and conjugated antibiotics in an estuarine food web based on multimedia fate and model simulation - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Yuan-Yue Cheng; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

Re-evaluating the impact of feeding shock on anaerobic co-digestion of food waste and waste activated sludge: Trade-off between efficiency and stability - Yaqian Liu; Qian Li; Mawuli Dzakpasu; Rong Chen; Yu-You Li (Chemical Engineering Journal, 2024)

Steroid metabolites as overlooked emerging contaminants: Insights from multimedia partitioning and source–sink simulation in an estuarine environment - Ru Xu; Shan Liu; Yun-Feng Pan; Nian-Nian Wu; Qian-Yi Huang; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Yuan-Yue Cheng (Journal of Hazardous Materials, 2024)

A co-located QTL for seven spike architecture-related traits shows promising breeding use potential in common wheat (Triticum aestivum L.) - Jieguang Zhou; Qian Liu; Rong Tian; Huangxin Chen; Jian Wang; Yaoyao Yang; Conghao Zhao; Yanlin Liu; Huaping Tang; Mei Deng; Qiang Xu; Qiantao Jiang; et al. (Theoretical and Applied Genetics, 2024)

Low-cost ZIF-67-modified fabrics with effective photothermal disinfection for antimicrobial personal protective equipment production - Nan Jiang; Qian Wang; Huiqiong Zhang; Ziwei Liu; Hao Yang; Rong Chen; Zhong Lu (Journal of Environmental Chemical Engineering, 2023)

Efficacy of pterostilbene suppression on Aspergillus flavus growth, aflatoxin B1 biosynthesis and potential mechanisms - Yong-Mei Hu; Yi-Rong Wang; Wen-Bin Zhao; Yan Yan Ding; Zheng-Rong Wu; Guang-Han Wang; Peng Deng; Shao-Yong Zhang; Jun-Xia An; Zhi-Jun Zhang; Xiong-Fei Luo; Ying-Qian Liu (International Journal of Food Microbiology, 2023)

Membrane fabrication and configuration design development of photothermal membrane distillation (PMD) - Guo-Rong Xu; Min Wang; Ke Xu; He-Li Zhao; Qian Liu (Desalination, 2023)

Multifunctional dumbbell probes-based logic circuits: microRNAs logic detection and tumor cells identification - Xin Liu; Baiying Li; Qian Liu; Li Zhang; Rong Zhao; Di Wu; Luojia Wang; Zhongzhong Wang; Guoming Xie; Wenli Feng (Analytica Chimica Acta, 2023)

Neuroglobin Facilitates Neuronal Oxygenation through Tropic Migration under Hypoxia or Anemia in Rat: How Does the Brain Breathe? - Chun-Yang Li; Hai-Feng Jiang; Li Li; Xiao-Jing Lai; Qian-Rong Liu; Shang-Bin Yu; Cheng-La Yi; Xiao-Qian Chen (Neuroscience Bulletin, 2023)

Urine 2-hydroxyphenanthrene is associated with current asthma: evidence from NHANES 2007–2012 - Lingyi Lu; Tingfeng Mao; Rui Xu; Lanxia Liu; Jiefeng Qian; Kai Yang; Anjie Yuan; Xinyue Wang; Rong Ni (International Archives of Occupational and Environmental Health, 2023)

Exploration for cobalt/nitrogen-doped catalyst to creatinine degradation via peroxymonosulfate activation: toxicity evaluation, statistical modeling, and mechanisms study - Jiadi Liu; Yawen Dong; Yu Kang; Qian Kong; Kuaibing Wang; Feifei Mao; Yuanqing Bu; Rong Zhou; Chunyong Zhang; Hua Wu (Environmental Science and Pollution Research, 2023)

A self-assembled nanoparticle vaccine based on pseudorabies virus glycoprotein D induces potent protective immunity against pseudorabies virus infection - Xujiao Ren; Nan Cao; Linxing Tian; Wenqiang Liu; Hechao Zhu; Zhenxiang Rong; Manman Yao; Xiangmin Li; Ping Qian (Veterinary Microbiology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Phloroglucinol derivatives, coumarins and an alkaloid from the roots of Evodia lepta Merr. - Xiao-Ying Ding; Jun-Ru Wen; Wei-Yao Lin; Guo-Yong Huang; Qian Feng; Lixin Duan; Shi-Jie Zhang; Zhongqiu Liu; Rong-Rong Zhang; Ying Wang (Phytochemistry, 2023)

Site-specific Atg13 methylation-mediated autophagy regulates epithelial inflammation in PM2.5-induced pulmonary fibrosis - Jie Ning; Zijie Pei; Mengruo Wang; Huaifang Hu; Meiyu Chen; Qingping Liu; Mengqi Wu; Peihao Yang; Zihan Geng; Jie Zheng; Zhe Du; Wentao Hu; et al. (Journal of Hazardous Materials, 2023)

Cadmium induced a non-coding RNA microRNA535 mediates Cd accumulation in rice - Erkui Yue; Fuxi Rong; Zhen Liu; Songlin Ruan; Tao Lu; Haifeng Qian (Journal of Environmental Sciences, 2023)

Daphnia magna uptake and excretion of luminescence‐labelled polystyrene nanoparticle as visualized by high sensitivity real-time optical imaging - Yu-Hang Zhang; Rong-Yao Gao; Ze-Jun Wang; Qian-Qian Shao; Ya-Wen Hu; Hua-Bing Jia; Xiao-Jing Liu; Feng-Qin Dong; Li-Min Fu; Jian-Ping Zhang (Chemosphere, 2023)

Coaxial electrospun nanofibrous substrates with tunable wettability for constructing cucurbit[n]uril-embedded organic solvent nanofiltration membranes - Qian Wang; Qin-Yuan He; Liu-Lin Zhao; Yue Wang; Rong Fang; Cong Luo; Wei-Tong Lu; Hong-Ya Jiang; Shi-Peng Sun; Xue-Li Cao (Chemical Engineering Journal, 2023)

The mechanisms of rapid seed germination in Caragana species adapted to low mean annual precipitation - Shi-Hua Qi; Guang-Qian Yao; Md. Mahadi Hasan; Hui Jiang; Xu-Dong Liu; Zheng-Fei Nie; Xia-Yi Zhang; Ya-Xian Du; Xue-Qian Tian; Feng-Ping Li; Xue-Rong Li; Xiang-Wen Fang (Trees, 2023)

Free and conjugated forms of metabolites are indispensable components of steroids: The first evidence from an estuarine food web - Shan Liu; Ru Xu; Yun-Feng Pan; Qian-Yi Huang; Nian-Nian Wu; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu (Water Research, 2023)

Enhanced microwave absorption capacity of iron-based catalysts by introducing Co and Ni for microwave pyrolysis of waste COVID-19 Masks - Chao Yuwen; Bingguo Liu; Qian Rong; Keren Hou; Libo Zhang; Shenghui Guo (Fuel, 2023)

Transcriptome sequencing and metabolite analysis reveal the single and combined effects of microplastics and di-(2-ethylhexyl) phthalate on Peneaus vannamei - Qiang-Qiang Shi; Xiao-Qian Zhang; Ze-Ming Zhang; Ning-Bo Wang; Hua Liu; Rong-Rong Zhang; Ai-Li Sun; Jiong Chen; Xi-Zhi Shi (Science of The Total Environment, 2023)

Polyphenolic-modified cellulose acetate membrane for bone regeneration through immunomodulation - Qing-Yi Zhang; Jie Tan; Kai Huang; Rong Nie; Zi-Yuan Feng; Chen-Yu Zou; Qian-Jin Li; Jun Chen; Ning Sheng; Bo-Quan Qin; Zhi-Peng Gu; Li-Min Liu; et al. (Carbohydrate Polymers, 2023)

Assessing the consistency of crop leaf area index derived from seasonal Sentinel-2 and Landsat 8 imagery over Manitoba, Canada - Taifeng Dong; Jane Liu; Jiangui Liu; Liming He; Rong Wang; Budong Qian; Heather McNairn; Jarrett Powers; Yichao Shi; Jing M Chen; Jiali Shang (Agricultural and Forest Meteorology, 2023)

Process parameters and biological mechanism of efficient removal of Cd(II) ion from wastewater by a novel Bacillus subtilis TR1 - Zhongbing Wang; Rong Tan; Jie Gong; Baichuan Gong; Qian Guan; Xue Mi; Di Deng; Xiangning Liu; Chunli Liu; Chunjian Deng; Chunlian Ding; Guisheng Zeng (Chemosphere, 2023)

Meal Skipping and Shorter Meal Intervals Are Associated with Increased Risk of All-Cause and Cardiovascular Disease Mortality among US Adults - Yangbo Sun; Shuang Rong; Buyun Liu; Yang Du; Yuxiao Wu; Liangkai Chen; Qian Xiao; Linda Snetselaar; Robert Wallace; Wei Bao (Journal of the Academy of Nutrition and Dietetics, 2023)

Aroma formation and transformation during sealed yellowing process of Pingyang yellow tea - Rong-Jian Dong; Xie-Huang Sheng; Qian-Tu Xie; Xiaolin Huang; Fujie Yan; Songbai Liu (Food Research International, 2023)

Lipid metabolic characteristics and marker compounds of ripened Pu-erh tea during pile fermentation revealed by LC-MS-based lipidomics - Jia Li; Haibo Yuan; Yuting Rong; Michael C. Qian; Fuqiao Liu; Jinjie Hua; Qinghua Zhou; Yuliang Deng; Jun Zeng; Yongwen Jiang (Food Chemistry, 2023)

Dorsal root ganglia P2X4 and P2X7 receptors contribute to diabetes-induced hyperalgesia and the downregulation of electroacupuncture on P2X4 and P2X7 - Qun-qi Hu; Xiao-fen He; Yi-qi Ma; Li-qian Ma; Si-ying Qu; Han-zhi Wang; Yu-rong Kang; Lu-hang Chen; Xiang Li; Bo-yu Liu; Xiao-mei Shao; Jun-fan Fang; et al. (Purinergic Signalling, 2023)

Erythropoietin promotes energy metabolism to improve LPS-induced injury in HK-2 cells via SIRT1/PGC1-α pathway - Kan Li; Li Gao; Sen Zhou; Yan-Rong Ma; Xiao Xiao; Qian Jiang; Zhi-Hong Kang; Ming-Long Liu; Tian-Xi Liu (Molecular and Cellular Biochemistry, 2023)

Biochar-assisted anaerobic membrane bioreactor towards high-efficient energy recovery from swine wastewater: Performances and the potential mechanisms - Gaojun Wang; Guohao Liu; Gaofei Yao; Peng Fu; Changxi Sun; Yu Li; Qian Li; Yu-You Li; Rong Chen (Bioresource Technology, 2023)

Green supply chain management for a more sustainable manufacturing industry in China: a critical review - Xuerou Sheng; Leping Chen; Xueliang Yuan; Yuzhou Tang; Qian Yuan; Rong Chen; Qingsong Wang; Qiao Ma; Jian Zuo; Hongwei Liu (Environment, Development and Sustainability, 2023)

Personalizing atomoxetine dosing in children with ADHD: what can we learn from current supporting evidence - Di Fu; Hong-Li Guo; Ya-Hui Hu; Wei-Rong Fang; Qian-Qi Liu; Jing Xu; Dan-Dan Wu; Feng Chen (European Journal of Clinical Pharmacology, 2023)

Mechanism of microwave-assisted iron-based catalyst pyrolysis of discarded COVID-19 masks - Chao Yuwen; Bingguo Liu; Qian Rong; Keren Hou; Libo Zhang; Shenghui Guo (Waste Management, 2023)

Boosting persulfate activation via paper mill sludge-based biochar for efficient degradation of bisphenol A: Inherent multiple active sites - Zhi-Juan Wang; Yang-Qian Lin; Hua-Jing Zhou; Zi-Lian Liu; Rong-Rong Miao; Xi-Meng Xu; Liang He; Qing-Qing Guan (Chemical Engineering Journal, 2023)

Coassisted carbonization with HCOOK/(HCOO)2Ca for the fabrication of bamboo-derived oxygen-doped porous carbons exhibiting high-performance sorption of diethyl phthalate from aqueous solutions - Fei Gu; Rongting Ji; Qian Sun; Shengcun Chen; Rong Bai; Yuying Shen; Xinran Liu; Yang Song; Jiangang Han; Xin Jiang; Hu Cheng; Jianming Xue (Bioresource Technology, 2023)

Exposure–response relationship between temperature, relative humidity, and varicella: a multicity study in South China - Yihan Li; Jialing Li; Zhihua Zhu; Weilin Zeng; Qi Zhu; Zuhua Rong; Jianxiong Hu; Xing Li; Guanhao He; Jianguo Zhao; Lihua Yin; Yi Quan; et al. (Environmental Science and Pollution Research, 2023)

Isolation and Analysis of Reverse Transcriptase of Ty1-copia-Like Retrotransposons in Sugarcane - Jun-Xian Liu; Jing Liu; Tai-Yi Yang; Li-Min Liu; Li-Hang Qiu; Yi-Jing Gao; Wei-Xing Duan; Jing-Chao Lei; Hong-Jian Liu; Rong-Hua Zhang; Wei-Zhong He; Song Li; et al. (Sugar Tech, 2022)

NGF/TrkA promotes the vitality, migration and adhesion of bone marrow stromal cells in hypoxia by regulating the Nrf2 pathway - Cui-Ni Fang; Hai-Qun Tan; Ao-Bo Song; Ni Jiang; Qian-Rong Liu; Tao Song (Metabolic Brain Disease, 2022)

SWI2/SNF2 chromatin remodeling ATPases SPLAYED and BRAHMA control embryo development in rice - Qian Xun; Min Mei; Ye Song; Chenyu Rong; Jiajun Liu; Tianhui Zhong; Yanfeng Ding; Chengqiang Ding (Plant Cell Reports, 2022)

Ventromedial Thalamus-Projecting DCN Neurons Modulate Associative Sensorimotor Responses in Mice - Jie Zhang; Hao Chen; Li-Bin Zhang; Rong-Rong Li; Bin Wang; Qian-Hui Zhang; Liu-Xia Tong; Wei-Wei Zhang; Zhong-Xiang Yao; Bo Hu (Neuroscience Bulletin, 2022)

The addition of sawdust reduced the emission of nitrous oxide in pig manure composting by altering the bacterial community structure and functions - Chao Liu; Jiao Yan; Qian Huang; Hongjun Liu; Cece Qiao; Rong Li; Biao Shen; Qirong Shen (Environmental Science and Pollution Research, 2022)

Predictive value of monocyte to HDL cholesterol ratio for stroke-associated pneumonia in patients with acute ischemic stroke - Yaming Sun; Juan Lu; Danni Zheng; Jufen Qian; Hongxin Zhang; Dong Xing; Fengdan Rong; Yongjun Cao; Chun-Feng Liu; Shoujiang You (Acta Neurologica Belgica, 2021)

Influencing factors and physiochemical changes of embryogenesis through in vitro isolated microspore culture in Brassica species - Yan-Qi Dong; Yu-Hong Gao; Te Zhao; Guang-Qian Ren; Yan-Li Liu; Bin Guan; Rong-Xian Jin; Fei Gao; Yan-Li Zhang; Xiu-Fang Tan; Hong-Cai Zhu; Yu-Hong Zhang; et al. (Biologia, 2021)

The intestine of artificially bred larval turbot (Scophthalmus maximus) contains a stable core group of microbiota - Zheng Zhang; Yongxiang Yu; Yan Jiang; Yingeng Wang; Meijie Liao; Xiaojun Rong; Qian Liu (Archives of Microbiology, 2020)

Small grain and semi-dwarf 3, a WRKY transcription factor, negatively regulates plant height and grain size by stabilizing SLR1 expression in rice - Jie Lan; Qibing Lin; Chunlei Zhou; Yakun Ren; Xi Liu; Rong Miao; Ruonan Jing; Changling Mou; Thanhliem Nguyen; Xingjie Zhu; Qian Wang; Xin Zhang; et al. (Plant Molecular Biology, 2020)

Retraction Note to: Ambient air pollution and adverse birth outcomes: a systematic review and meta-analysis - Le-qian Guo; Yu Chen; Bai-bing Mi; Shao-nong Dang; Dou-dou Zhao; Rong Liu; Hong-li Wang; Hong Yan (Journal of Zhejiang University-SCIENCE B, 2020)

Translocator protein 18 kDa: a potential therapeutic biomarker for post traumatic stress disorder - Zhi-Kun Qiu; Xu Liu; Yong Chen; Rong-Jia Wu; Shi-Feng Guan; Yun-yun Pan; Qian-Bo Wang; Dan Tang; Tao Zhu; Ji-Sheng Chen (Metabolic Brain Disease, 2020)

Physiological and proteomic responses of mangrove plant Avicennia marina seedlings to simulated periodical inundation - Huan Li; Zan Li; Zhi-Jun Shen; Mei-Rong Luo; Yi-Ling Liu; Ming-Yue Wei; Wen-Hua Wang; Ying-Ying Qin; Chang-Hao Gao; Ke-Ke Li; Qian-Su Ding; Shan Zhang; et al. (Plant and Soil, 2020)

Effects of Exogenous GA3 and DPC Treatments on Levels of Endogenous Hormone and Expression of Key Gibberellin Biosynthesis Pathway Genes During Stem Elongation in Sugarcane - Li-Hang Qiu; Rong-Fa Chen; Han-Min Luo; Ye-Geng Fan; Xing Huang; Jun-Xian Liu; Fa-Qian Xiong; Hui-Wen Zhou; Chong-Kun Gan; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2019)

Paramyxoviruses respiratory syncytial virus, parainfluenza virus, and human metapneumovirus infection in pediatric hospitalized patients and climate correlation in a subtropical region of southern China: a 7-year survey - Wen-Kuan Liu; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Li Zhang; Shu-Jun Gu; Rong Zhou; Qian Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Calcium intake and colon cancer risk subtypes by tumor molecular characteristics - NaNa Keum; Li Liu; Tsuyoshi Hamada; Zhi Rong Qian; Jonathan A. Nowak; Yin Cao; Annacarolina da Silva; Keisuke Kosumi; Mingyang Song; Daniel Nevo; Molin Wang; Andrew T. Chan; et al. (Cancer Causes & Control, 2019)

New pyrazinoquinazoline alkaloids Isolated from a culture of Stenotrophomonas maltophilia QB-77 - Sheng-Yan Qian; Cai-Ling Yang; Afsar Khan; Rong-Xiang Chen; Ming-Song Wu; Li Tuo; Qian Wang; Jian-Guo Liu; Gui-Guang Cheng (Natural Product Research, 2019)

Candida glabrata-Induced Refractory Infectious Arthritis: A Case Report and Literature Review - Shu Chen; Yi Chen; Yi-qin Zhou; Ning Liu; Rong Zhou; Jin-hui Peng; Qi-rong Qian (Mycopathologia, 2019)

RETRACTED ARTICLE: Ambient air pollution and adverse birth outcomes: a systematic review and meta-analysis - Le-Qian Guo; Yu Chen; Bai-Bing Mi; Shao-Nong Dang; Dou-Dou Zhao; Rong Liu; Hong-Li Wang; Hong Yan (Journal of Zhejiang University-SCIENCE B, 2019)

Anti-senescence effect and molecular mechanism of the major royal jelly proteins on human embryonic lung fibroblast (HFL-I) cell line - Chen-min Jiang; Xin Liu; Chun-xue Li; Hao-cheng Qian; Di Chen; Chao-qiang Lai; Li-rong Shen (Journal of Zhejiang University-SCIENCE B, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Variations in High-frequency Oscillations of Tropical Cyclones over the Western North Pacific - Shumin Chen; Weibiao Li; Zhiping Wen; Mingsen Zhou; Youyu Lu; Yu-Kun Qian; Haoya Liu; Rong Fang (Advances in Atmospheric Sciences, 2018)

MEF2D Mediates the Neuroprotective Effect of Methylene Blue Against Glutamate-Induced Oxidative Damage in HT22 Hippocampal Cells - Zi-wei Chen; Anmin Liu; Qingyu Liu; Jingkao Chen; Wen-ming Li; Xiao-juan Chao; Qian Yang; Pei-qing Liu; Zi-xu Mao; Rong-biao Pi (Molecular Neurobiology, 2017)

Use of stable isotopes to understand food webs in Macao wetlands - Qian Chen; Yang Liu; Wei-Tim Ho; Shek Kiu Chan; Qiu-hua Li; Jian-Rong Huang (Wetlands Ecology and Management, 2017)

Dual-Labeled Time-Resolved Immunofluorometric Assay for the Simultaneous Quantitative Detection of Hepatitis B Virus Antigens in Human Serum - Rong-Liang Liang; Yun-Sen Yang; Jian-Wei Zhou; Tian-Cai Liu; Xu-Ping Xu; Qian-Ni Liang; Zhen-Hua Chen; Zhi-Ning Dong; Ying-Song Wu (Journal of Fluorescence, 2017)

Erratum to: Injection of Aβ1-40 into hippocampus induced cognitive lesion associated with neuronal apoptosis and multiple gene expressions in the tree shrew - Na Lin; Liu-Lin Xiong; Rong-ping Zhang; Hong Zheng; Lei Wang; Zhong-Yi Qian; Piao Zhang; Zhi-wei Chen; Fa-Bao Gao; Ting-Hua Wang (Apoptosis, 2016)

Injection of Aβ1-40 into hippocampus induced cognitive lesion associated with neuronal apoptosis and multiple gene expressions in the tree shrew - Na Lin; Liu-Lin Xiong; Rong-ping Zhang; Hong Zheng; Lei Wang; Zhong-Yi Qian; Piao Zhang; Zhi-wei Chen; Fa-Bao Gao; Ting-Hua Wang (Apoptosis, 2016)

Large-scale comparative phosphoprotein analysis of maize seedling leaves during greening - De-Li Ning; Ke-Hui Liu; Chang-Cai Liu; Jin-Wen Liu; Chun-Rong Qian; Yang Yu; Yue-Feng Wang; Ying-Chun Wang; Bai-Chen Wang (Planta, 2016)

CDK14 Contributes to Reactive Gliosis via Interaction with Cyclin Y in Rat Model of Spinal Cord Injury - Chengwei Duan; Yonghua Liu; Lu Lu; Rixin Cai; Huaqing Xue; Xingxing Mao; Chen Chen; Rong Qian; Dongmei Zhang; Aiguo Shen (Journal of Molecular Neuroscience, 2015)

RNAi Knockdown of Hypoxia-Inducible Factor-1α Decreased the Proliferation, Migration, and Invasion of Hypoxic Hepatocellular Carcinoma Cells - ChengShi Chen; Rong Liu; JianHua Wang; ZhiPing Yan; Sheng Qian; Wei Zhang (Cell Biochemistry and Biophysics, 2015)

The Effects of Fludarabine on Rat Cerebral Ischemia - Qian Xu; Chunjuan Jiang; Yutao Rong; Chun Yang; Ying Liu; Kai Xu (Journal of Molecular Neuroscience, 2015)

De novo analysis of the Tenebrio molitor (Coleoptera: Tenebrionidae) transcriptome and identification of putative glutathione S-transferase genes - Su Liu; Xiao-Xiao Shi; Yan-Dong Jiang; Zi-Jie Zhu; Ping Qian; Min-Jing Zhang; Hang Yu; Qing-Zi Zhu; Zhong-Jun Gong; Zeng-Rong Zhu (Applied Entomology and Zoology, 2015)

Trehalose Metabolism-Related Genes in Maize - Mei-Liang Zhou; Qian Zhang; Zhan-Min Sun; Li-Hui Chen; Bo-Xin Liu; Kai-Xuan Zhang; Xue-Mei Zhu; Ji-Rong Shao; Yi-Xiong Tang; Yan-Min Wu (Journal of Plant Growth Regulation, 2014)

Light-regulated phosphorylation of maize phosphoenolpyruvate carboxykinase plays a vital role in its activity - Qing Chao; Xiao-Yu Liu; Ying-Chang Mei; Zhi-Fang Gao; Yi-Bo Chen; Chun-Rong Qian; Yu-Bo Hao; Bai-Chen Wang (Plant Molecular Biology, 2014)

Neuroglobin Promotes Neurite Outgrowth via Differential Binding to PTEN and Akt - Li Li; Qian Rong Liu; Xin Xin Xiong; Ju Mei Liu; Xiao Jing Lai; Chun Cheng; Feng Pan; Yong Chen; Shang Bin Yu; Albert Cheung Hoi Yu; Xiao Qian Chen (Molecular Neurobiology, 2014)

Differences in oxidative stress, antioxidant systems, and microscopic analysis between regenerating callus-derived protoplasts and recalcitrant leaf mesophyll-derived protoplasts of Citrus reticulata Blanco - Xiaoyong Xu; Gaisheng Xie; Li He; Jiaojiao Zhang; Xiaoling Xu; Rong Qian; Guohua Liang; Ji-Hong Liu (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

PTP1B inhibitor improves both insulin resistance and lipid abnormalities in vivo and in vitro - Yi-ming Ma; Rong-ya Tao; Qian Liu; Juan Li; Jin-ying Tian; Xiao-lin Zhang; Zhi-yan Xiao; Fei Ye (Molecular and Cellular Biochemistry, 2011)

Production of conjugated linoleic acids by Lactobacillus plantarum strains isolated from naturally fermented Chinese pickles - Pei Liu; Sheng-rong Shen; Hui Ruan; Qian Zhou; Liu-liu Ma; Guo-qing He (Journal of Zhejiang University-SCIENCE B, 2011)

Effect of dietary fatty acids on serum parameters, fatty acid compositions, and liver histology in Shaoxing laying ducks - Wei-meng Liu; Shu-jing Lai; Li-zhi Lu; Fang-xiong Shi; Jing Zhang; Yu Liu; Bo Yu; Zheng-rong Tao; Jun-da Shen; Guo-qin Li; De-qian Wang; Jin-jun Li; et al. (Journal of Zhejiang University-SCIENCE B, 2011)

2ME and 2OHE2 exhibit growth inhibitory effects and cell cycle arrest at G2/M in RL95-2 human endometrial cancer cells through activation of p53 and Chk1 - Qian-fen Gong; E-hu Liu; Rong Xin; Xiuning Huang; Ning Gao (Molecular and Cellular Biochemistry, 2011)

Effects of allicin on CYP2C19 and CYP3A4 activity in healthy volunteers with different CYP2C19 genotypes - Li-Jun Yang; Lan Fan; Zhao-Qian Liu; Yan-Mei Mao; Dong Guo; Li-Hui Liu; Zhi-Rong Tan; Liang Peng; Chun-Ting Han; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Synergistic induction of tumor cell death by combining cisplatin with an oncolytic adenovirus carrying TRAIL - Qiuwei Pan; Bisheng Liu; Jin Liu; Rong Cai; Yigang Wang; Cheng Qian (Molecular and Cellular Biochemistry, 2007)

Synthesis and insecticidal activities of novel derivatives of podophyllotoxin - Ying-Qian Liu; Liu Yang; Yanqing Liu; Xudong Di; Hang Xiao; Xuan Tian; Rong Gao (Natural Product Research, 2007)

Suppression of colorectal tumor growth by regulated survivin targeting - Binghua Li; Junkai Fan; Xinran Liu; Rong Qi; Linan Bo; Jinfa Gu; Cheng Qian; Xinyuan Liu (Journal of Molecular Medicine, 2006)

Use of fluorometry for determination of skim milk powder adulteration in fresh milk - Rong-fa Guan; Dong-hong Liu; Xing-qian Ye; Kai Yang (Journal of Zhejiang University-SCIENCE B, 2005)